Performance of biocompatible PEEK processed by fused deposition additive manufacturing. (15th May 2018) - Arif, M.F.; Kumar, S.; Varadarajan, K.M.; Cantwell, W.J.
Abstract: In this study, the tensile, flexural and fracture behavior of PEEK processed by fused filament fabrication (FFF) is reported. Three different configurations, viz., specimens built horizontally with a raster angle of 0° (H-0°) and 90° (H-90°), and vertically with a raster angle of 90° (V-90°) are examined. The best performing specimen in terms of its tensile, flexural and fracture toughness properties is H-0°, followed by H-90° and V-90°. The H-0° and H-90° specimens exhibit 85% and 75% of tensile and flexural strengths of molded bulk PEEK, respectively. The fracture toughnesses of the H-0° and H-90° specimens are 78% and 70% of molded bulk PEEK, respectively. However, V-90° specimens show lower tensile, flexural and fracture toughness properties compared to those of H-0°, H-90° and molded PEEK. The fracture surface and microtomography analyses indicate that the degree of interfacial bonding between beads during layer-by-layer buildup, is affected by the thermal gradient across the beads. The PEEK specimen configurations examined here have different thermal gradient in the build directions and such variations manifest themselves in their macroscopic mechanical behavior. The findings of this study provide guidelines for FFF of PEEK to enable its realization in applications such as orthopedic implants. Graphical abstract: Unlabelled Image Highlights: Horizontally 3D printed PEEK with raster angles of 0 o and 90 o exhibits tensile flexural and fracture properties comparable to those of molded PEEK Specimens built vertically are prone to delamination, exhibiting poorer mechanical performance due to high thermal gradient in the build-direction Stick-slip fracture and lower Poisson's ratio are observed for specimens built vertically, due to the presence of interfacial voids. Minimizing thermal gradients across beads is the key to producing parts with excellent macroscopic properties